Clinical Impact of Liquid Biopsy in Prostatic Cancer: A Literature Review - Mohamed Hussein; Hiba Ismail (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
The most prev amost prev abstract alent solid tumor in men worldwide is prostate cancer. The need for biomarkers to guide management choices is critical given the frequency of prostate cancer and its relatively lengthy clinical course. Based on a patient's unique risk stratification, which considers pathologic characteristics from a prostate biopsy, prostate-specific antigen (PSA) level, imaging, and other patient factors, decisions about localized prostate cancer treatment options, such as active surveillance, surgical excision, or targeted radiation, are made. An attractive method for thorough cancer analysis is to use